Assistance to postpartum mothers using the Home Care method on Personal Hygiene and Breast Care in Kebun Hamlet and Congaban Hamlet, Samiran Village, Proppo Subdistrict, Pamekasan Regency - Ilatus Zahroh; Emi Yunita (LP4M STIKes Karsa Husada Garut, 2023)
Postpartum infections are one of the leading causes of maternal mortality in developing countries. Personal hygiene in postpartum mothers is very important so that they are not vulnerable to infection. This service activity has a direction to improve skills in maintaining personal hygiene and performing breast self-care in postpartum women with the target of activities being a group of postpartum women in the garden hamlet and congaban hamlet of Samiran village, Proppo sub-district, Pamekasan district. The method used is by providing assistance to postpartum women door to door about personal hygiene and breast care. The results obtained are that after home care assistance, postpartum women understand the causes, signs and symptoms and prevention of postpartum infections through good personal hygiene and proper breast care. From counseling activities on personal hygiene and breast care in postpartum mothers, it is very useful, especially for mothers who have children for the first time (primipara). The delivery of material and demonstrating breast care is very influential in improving midwifery care services for postpartum women. Counseling on personal hygiene and breast care by health workers is very useful to increase the knowledge and skills of postpartum women in performing personal hygiene and breast care independently after childbirth.